METHODICAL PROBLEMS OF THE E-LEARNING OF PHYSICS BY THE MEANS OF INTERNET TECHNOLOGIES (Journal of Information Technologies in Education (ITE), 2012)
The article describes the processes of the studying method's transformations and the role of the teacher in them; highlights the basic difficulties related with these changes and represented the technical and methodical means of overcoming them.
Keywords: e-learning; facilitation